2017
DOI: 10.1504/ijtpm.2017.083740
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences and knowledge acquisition capability in joint ICT project teams in Malaysia

Abstract: This study investigates the underlying differences in individual knowledge acquisition capabilities. Drawing on the individual dimension of absorptive capacity, we clarify the antecedents of local team member's capability to acquire foreign partner's knowledge in joint ICT project team. Specifically, we proposed prior experience, learning goal orientation and need for cognition as antecedents to local employee's abilities to (1) recognise the value of and (2) assimilate foreign partner's knowledge. The hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
1
3
0
Order By: Relevance
“…The teacher's expertise has a low-level influence on knowledge acquisition. This is quite consistent with the qualitative research results of the thesis on professional knowledge factors and in accordance with the studies of Ojo & Raman (2017) and Rowold (2007).…”
Section: Discussing Quantitative Research Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The teacher's expertise has a low-level influence on knowledge acquisition. This is quite consistent with the qualitative research results of the thesis on professional knowledge factors and in accordance with the studies of Ojo & Raman (2017) and Rowold (2007).…”
Section: Discussing Quantitative Research Resultssupporting
confidence: 91%
“…(ii) Receiving knowledge from outside through international cooperation, association, joint venture, or consulting project with knowledge givers and receivers belonging to two different organizations (Dao & Nguyen, 2016, Ojo & Raman, 2017.…”
Section: Research Overview Of Factors Affecting the Acquisition Of Pe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Extant research in ACAP has found that existing knowledge bases of individuals serve as antecedents for their ability to acquire and assimilate new knowledge and hence their ACAP (Cohen and Levinthal, 1990). In the context of joint ICT project teams in Malaysia, Ojo and Raman (2015, 2017) find that LGO is a key antecedent of IACAP along with prior knowledge and the need for cognition. Similarly, examining joint project teams in the Nigerian upstream oil industry, Ojo et al.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 97%